Perception and Motivation of Prospective Chemistry Teachers in Online Learning during COVID-19 Pandemic: A Case of Lampung University - Sunyono, Sunyono; Meristin, Annisa; Prabowo, Galuh Catur Wisnu (FKIP Universitas Lampung, 2021)
The importance of this research is to get to know the students’ perceptions and motivation of the prospective chemistry teachers in facing online learning during the Covid-19 pandemic. The research design used was descriptive qualitative research. The research was conducted on students of the Chemistry Education Study Program FKIP University of Lampung in 2017, 2018, and 2019. Data collection was carried out by using a questionnaire by means of google form and learning record data in the online data-log mode edusmart.fkip.unila.ac.id. and vclass.unila.ac.id. The results indicated that (1) the interaction pattern between the lecturers and students was quite good in terms of giving assignments and discussions. In terms of feedback and learning reflection, it, however, needs to be improved (2) Students' perception of online learning is less positive, this is indicated by the number of students who are disappointed because of learning methods un-interactive, (3) students are still not motivated yet to take online lectures due to limitation of internet signals and seem to consider it as assignments only. Keywords: COVID-19 pandemic, online learning, motivation, perception. DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp77-89